Identification of natural products and their derivatives as promising inhibitors of protein glycation with non-toxic nature against mouse fibroblast 3T3 cells - Ghulam Abbas; Ahmed Suliman Al-Harrasi; Hidayat Hussain; Samina Abdul Sattar; M. Iqbal Choudhary (International Journal of Phytomedicine, 2016)
This study was performed to identify new inhibitors of protein glycation in vitro. Protein glycation is one of the major causes of late diabetic complications. In this study, terpenoids and alkaloids, isolated from different medicinal plants, along with their derivatives, were evaluated for their antiglycation activity in vitro, while MTT assay on mouse fibroblast 3T3 cells was used to assess their potential cytotoxicity. Among the tested compounds, gossypol (2,2′-bis-(formyl-1,6,7-trihydroxy-5-isopropyl-3-methylnaphthalene) (1), isolated from Gossypium herbaceum, and its derivatives, gossypol acetic acid (2), gossypolidene- 4-aminoantipyrine (4), and gazolidone (6), showed a potent antiglycation activity (IC50 < 16 µM), while gossypolidene-4-aminoantipyrine (5) showed a significant antiglycation activity with IC50 value 82.934±2.924 µM, in BSA-fluorescence assay. Alkaloid, noscapine (3S)-6,7-Dimethoxy-3-[(5R)-4-methoxy-6-methyl-5,6,7,8-tetrahy-dro-1,3-dioxolo[4,5-g]isoquinolin-5-yl] isobenzofuran-1(3H)-one (7), isolated from Papaver somniferum, N-nitrosoaphyllinic acid (9), a derivative of alkaloid aphylline, and 2H-quinolizine, octahydro salt (11), a salt of alkaloid lupinine, exhibited significant inhibition activity with IC50 values 152.662±5.432, 393.758 ±4.001 µM and 110.203±4.816µM, respectively. Similarly, compounds gossypolidene thiocarbamide (3), deoxypeganine hydrochloride (8), lupinine (10) and cytisine (12) showed moderate inhibition with IC50 values of 401.865 ±18.450, 863.322 ±6.415, 712.176±7.745, and 728.462±2.331 µM, respectively. The results were compared with the standard antiglycation agent, rutin (13) (IC50 =98.012±2.030 µM). Cellular cytotoxicity assay showed only gossypol acetic acid (2) and gossypolidene thiocarbamide (3) as somewhat toxic to 3T3 (mouse fibroblast) cells with IC50 values 2.07 ±0.61 and 5.00 ±1.89 µM, respectively. Cycloheximide was used as a standard in this assay with IC50 value 0.3 ± 0.089 μM